Do adverts increase the probability of finding online cognitive behavioural therapy for depression? Cross-sectional study. Issue 2 (16th April 2012) - Jones, Ray B; Goldsmith, Lesley; Hewson, Paul; Kamel Boulos, Maged N; Williams, Christopher J
Abstract : Objective: To estimate the effect of online adverts on the probability of finding online cognitive behavioural therapy (CBT) for depression. Design: Exploratory online cross-sectional study of search experience of people in the UK with depression in 2011. (1) The authors identified the search terms over 6 months entered by users who subsequently clicked on the advert for online help for depression. (2) A panel of volunteers across the UK recorded websites presented by normal Google search for the term 'depression'. (iii) The authors examined these websites to estimate probabilities of knowledgeable and naive internet users finding online CBT and the improved probability by addition of a Google advert. Participants: (1) 3868 internet users entering search terms related to depression into Google. (2) Panel, recruited online, of 12 UK participants with an interest in depression. Main outcome measures: Probability of finding online CBT for depression with/without an advert. Results: The 3868 users entered 1748 different search terms but the single keyword 'depression' resulted in two-thirds of the presentations of, and over half the 'clicks' on, the advert. In total, 14 different websites were presented to our panel in the first page of Google results for 'depression'. Four of the 14 websites had links enabling access to online CBT in three clicks for knowledgeable users. Extending this approach to the 10 most frequent search terms, the authors estimated probabilities of finding online CBT as 0.29 for knowledgeable users and 0.006 for naive users, making it unlikely CBT would be found. Adding adverts that linked directly to online CBT increased the probabilities to 0.31 (knowledgeable) and 0.02 (naive). Conclusions: In this case, online CBT was not easy to find and online adverts substantially increased the chance for naive users. Others could use this approach to explore additional impact before committing to long-term Google AdWords advertising budgets. Trial registration: This exploratory case study was a substudy within a cluster randomised trial, registered on http://www.clinicaltrials.gov (reference: NCT01469689 ). (The trial will be reported subsequently).